Leadership Style and Effectiveness Among Management Students: A Comparative Study Among Two University (Journal of Business and Management, 2022)
In Indonesia, the vision mission statement and curriculum of university are varied. There may be differences perspective of leadership style among the management students that came from different vision, mission, and curriculum of a university. This research aims to do comparative study of the leadership style and effectiveness of two different universities management students in Indonesia using Situational Leadership Model by Hersey and Blanchard. This research was conducted by distributing LEAD questionnaires that already being adapted to management students of ITB and USU. The research samples consist of the total number of 180 students from the two universities. The answer from the questionnaires interpreted by the table matrix. The effectiveness score compared by using T-test from SPSS. The result of this comparative study shown that management students from ITB and USU have the same dominant leadership style that is Coaching Style. This research also finds that both universities’ management students still indicate a low level of leadership style effectiveness and adaptability leadership. Based on the result of this research, both universities expected to encourage students to learn and understand deeply about situational leadership style.Keywords: Comparative Study, Situational Leadership Model, Management Students